PENERAPAN METODE VIKOR PADA SISTEM PENUNJANG KEPUTUSAN UNTUK PEMILIHAN SEPEDA MOTOR BEKAS TERBAIK (Studi Kasus: Jogya Motor) - Dhela Widiastuti; Jupron (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
VIKOR VIseKriterijumska Optimizacija I Kompromisno Resenje method, is an approach in decision support system that aims to determine the optimal solution among various alternatives. Specifically designed to handle the complexity and diversity of criteria in decision making, this method provides a compromise solution that assists decision makers in selecting the option that best suits their preferences and constraints. In the context of used motorcycle selection, this process involves evaluating various aspects such as engine condition, kilometers traveled, year of manufacture, brand and price. The VIKOR method is used to rank a number of used motorcycle alternatives based on these criteria, which are the main considerations for potential buyers. The use of a Decision Support System (DSS) is considered an effective solution to assist in determining the best used motorcycle choice.